ANALYSIS OF LIBERAL FEMINISM ON MULAN 2020 MOVIE - Rizkianti Puspita Sari; Maya Kurnia Dewi (Universitas Ngudi Waluyo, 2025)
The 2020 live-action adaptation of Mulan offers a contemporary reinterpretation of the classic Disney animated film, presenting a nuanced portrayal of gender roles and feminist values. This analysis examines the film through the lens of liberal feminism, focusing on how the narrative and character development align with the principles of individual rights and gender equality. The film depicts Mulan as a strong, independent woman who challenges traditional gender roles and societal expectations. Key scenes, such as Mulan's decision to disguise herself as a man and her subsequent success in traditionally male-dominated roles, highlight the film's alignment with liberal feminist values. The analysis also considers the role of supporting characters, like the witch Xian Lang, and the depiction of patriarchal authority through figures like the Emperor. Despite its progressive elements, the film faces criticism for cultural inaccuracies and the reinforcement of certain stereotypes. Suggestions for future adaptations include enhancing cultural accuracy, exploring a broader range of feminist themes, and expanding representation across genres. By addressing these limitations, future films can further advance discussions on gender equality and representation in popular media .